A complexa teia da neutralidade espanhola durante a Segunda Guerra Mundial e a cobertura do Jornal Correio - Neuber, Thomaz Radino (2023)
The study aims to analyze some aspects of Spanish neutrality during the Second World War (1939-1945). It is about realizing the main reasons that led the country to remain neutral in the world conflict, considering the issue of the enclave of Gibraltar and the political point of view of the newspaper Correio Paulistano in the face of Spanish neutrality. Our aim was to investigate how the newspaper Correio Paulistano interpreted the Spanish posture and the interpretation of its neutrality. For that, correspondence exchanges between the rulers of Spain, Italy and Germany were analyzed, together with the analysis of books that addressed the subject and the archive newspaper Correio Paulistano. It can be concluded that through the investigated sources, Francisco Franco's Spain maintained the title of "neutral" throughout the conflict but maintained relations that favored itself and the axis countries. At the same time, the enclave of Gibraltar served as a strategy for Franco to postpone his country's entry into the war. Based on the analysis of the newspaper Correio Paulistano, we can conclude that it initially had a more favorable attitude towards the Spanish government. However, the posture changed as the war turned against the axis countries and after the conflict, he adopted a more critical attitude towards the Spanish caudillo